Effects and mechanisms of natural alkaloids for prevention and treatment of osteoporosis - Lin, Bingfeng; Xu, Pingcui; Zheng, Juan; Deng, Xuehui; Ye, Qitao; Huang, Zhongping; Wang, Nani (Frontiers in Pharmacology, 2022)
Natural alkaloids are polycyclic, nitrogen-containing, and basic compounds obtained from plants. In this review, the advances in bioactive alkaloids with respect to their chemical structures, herbal sources, and effects for the prevention and treatment of osteoporosis are discussed. Anti-osteoporosis alkaloids are classified into six categories based on the chemical structure, namely, isoquinoline alkaloids, quinolizidine alkaloids, piperidine alkaloids, indole alkaloids, pyrrolizidine alkaloids and steroidal alkaloids. They promote mesenchymal stem cells differentiation, improve osteoblast proliferation, stimulate osteoblast autophagy and suppress osteoclast formation. These natural alkaloids can regulate multiple signaling pathways, including interrupting the tumor necrosis factor receptor associated factor 6- receptor activator of nuclear factor kappa B interaction, inhibiting the nuclear factor kappa B pathway in osteoclasts, activating the p38 mitogen-activated protein kinases pathway in osteoblasts, and triggering the wingless and int-1 pathway in mesenchymal stem cells. This review provides evidence and support for novel drug and clinical treatment of osteoporosis using natural alkaloids.